Impact of an interprofessional transition of care service on 30-day hospital reutilizations. Issue 1 (2nd January 2019) - Otsuka, Shelley; Smith, Jennifer N.; Pontiggia, Laura; Patel, Radha V.; Day, Susan C.; Grande, David T.
ABSTRACT: The objective of this study was to evaluate the impact of an interprofessional Transitions of Care (TOC) service on 30-day hospital reutilization inclusive of hospital readmissions and ED visits. This was a retrospective cohort study including patients discharged from an academic medical center between September 2013 and October 2014. Patients scheduled for a hospital follow-up visit in the post-acute care clinic (PACC) were included in the intervention group and patients without a post-discharge interprofessional TOC service were included in the comparison group. The intervention included a hospital follow-up visit with an interprofessional healthcare team. The primary composite outcome was hospital reutilization, defined as a hospital readmission or ED visit within 30 days of the discharge date. Overall, 330 patients were included in each group. In the intention-to-treat analysis, the primary composite outcome was not significantly different between groups (16.97% vs. 19.39%, P = 0.4195) whereas in the per-protocol analysis (all patients who showed to their PACC appointment), the primary outcome was significantly different in favor of the intervention group (9.28% vs. 19.39%, P = 0.0009). When components were analyzed separately, there was a statistically significant difference in favor of intervention group for hospital readmissions, but there was no difference for ED visits. This study demonstrates that an outpatient interprofessional TOC service with patient engagement from a team of nurses, pharmacists, physicians, and social workers may reduce 30-day hospital readmissions but may not impact 30-day ED visits.